Acetyl-L-Carnitine Induces Autophagy to Promote Mouse Spermatogonia Cell Recovery after Heat Stress Damage. (19th January 2021) - Qiao, Na; Chen, Hanming; Du, Peiquan; Kang, Zhenlong; Pang, Congying; Liu, Bingxian; Zeng, Qiwen; Pan, Jiaqiang; Zhang, Hui; Mehmood, Khalid; Tang, Zhaoxin; Li, Ying
Abstract : Acetyl-L-carnitine (ALC) is an effective substrate for mitochondrial energy metabolism and is known to prevent neurodegeneration and attenuate heavy metal-induced injury. In this study, we investigated the function of ALC in the recovery of mouse spermatogonia cells (GC-1 cells) after heat stress (HS). The cells were randomly divided into three groups: control group, HS group (incubated at 42°C for 90 min), and HS + ALC group (treatment of 150 μ M ALC after incubated at 42°C for 90 min). After heat stress, all of the cells were recovered at 37°C for 6 h. In this study, the content of intracellular lactate dehydrogenase (LDH) in the cell supernatant and the malondialdehyde (MDA) levels, catalase (CAT) levels, and total antioxidant capacity (T-AOC) were significantly increased in the HS group compared to the CON group. In addition, the mitochondrial membrane potential (MMP) was markedly decreased, while the apoptosis rate and the expression of apoptosis-related genes (Bcl-2, Bax, and caspase3) were significantly increased in the HS group compared to the CON group. Furthermore, the number of autophagosomes and the expression of autophagy-related genes (Atg5, Beclin1, and LC3II) and protein levels of p62 were increased, but the expression of LAMP1 was decreased in the HS group compared to the CON group. However, treatment with ALC remarkably improved cell survival and decreased cell oxidative stress. It was unexpected that levels of autophagy were markedly increased in the HS + ALC group compared to the HS group. Taken together, our present study evidenced that ALC could alleviate oxidative stress and improve the level of autophagy to accelerate the recovery of GC-1 cells after heat stress.